Limbs and trunk soft tissue sarcoma systematic local and remote monitoring by MRI and thoraco-abdomino-pelvic scanner: A single-centre retrospective study. Issue 7 (July 2019) - De Angelis, Floriane; Guy, France; Bertaut, Aurélie; Méjean, Nathalie; Varbedian, Olivier; Hervieu, Alice; Truc, Gilles; Thibouw, David; Barra, Céline Charon; Fraisse, Jean; Burnier, Pierre; Isambert, Nicolas; et al.
Abstract: Introduction: Soft tissue sarcomas (STS) are rare malignant tumors that require management by an expert center. Monitoring modalities are not consensual. The objective of our study is to report systematic radiological monitoring data obtained by local MRI and by thoracic-abdominal-pelvic computed tomography (TAP CT). Material and methods: 113 consecutive patients managed at "Centre Georges François Leclerc, Dijon", between 2008 and 2016, for an initially localized STS were included. Patient follow-up consisted of a local MRI and a TAP CT. Follow-up exams schedule was initially every 4 months during 2 years, followed by every 6 months during 3 years and finally every year during 5 years. Results: Median follow-up time was 37.2 months [min = 2.4 – max = 111.6]. After 5 years of surveillance, local recurrence (LR) rate was 8.8% and diagnosed by imaging in 60% of cases. No deep LR was clinically found. Median LR diagnosis time was 23.9 months [min = 2.0 – max = 52.4]. 50% of patients locally treated for their LR were alive without recurrence. Metastatic recurrence (MR) rate was 31%. 42.8% had extra-pulmonary involvement and 17.1% had exclusive extrathoracic metastases. The median time to diagnosis of MR was 17.4 months [min = 2.7- max = 77.2]. High-grade tumors relapsed more (20.4%) and earlier (all before the 5th year) than low grade. Conclusion: Local MRI seems particularly suitable for monitoring deep tumors. In addition, the systematic monitoring by TAP CT highlighted a limited number of cases of exclusive extrathoracic metastases. The schedule of local and remote monitoring should primarily be adjusted to tumor grade.